PERBEDAAN MOTIVASI BELAJAR DAN MOTIVASI BERPRESTASI PADA MAHASISWA KELAS REGULER DENGAN KELAS BEASISWA GUBERNUR TERHADAP PRESTASI BELAJAR - Ririn Anggraini (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2012)
The differences of the input, school fee, and purpose between the regular and governor’s scholarship class may influence the collegian’s motivation both in learning and accomplising the achievement. The difference of the motivation between the two groups of the collegians itself will also influence their learning achievement.The purpose of this research is to know about the differences of the learning and achievement motivation of the collegian both in regular and governor’s scholarship class to their learning achievement in DIII Kebidanan Politeknik Kesehatan Kemenkes Bandung study program. Analysis comparative with Cross sectional approach is used as the research method in this paper. The learning and achievement motivation data is collected through the questionnaire, while the learning achievement data is collected through documentation. The data analysis is examined by using T test, Mann Whitney, and rank spearman correlation.The result of the research shows the difference of achievement motivation ( p= 0,003 < 0,05) and learning achievement ( p= 0,000< 0,05), but it does not show a meaningful difference in the learning motivation (p= 0, 263 > 0,05), in the regular class shows the correlation between the achievement motivation and learning achievement (p< 0,05) with low correlation (rs= 0,370), but there is no meaningful correlation between the learning motivation and learning achievement (p> 0,05) both in regular and governor’s scholarship class From the result of the research, the writer can conclude that there is a difference in achievement motivation and learning achievement of the regular and governors’ scholarship class. The correlation between the achievement motivation and learning achievement has only been found in the collegian of the regular class.